Base Broadening for client-oriented impact - Sperling, L.; Ashby, Jacqueline A.; Weltzien, Eva; Smith, M.; McGrath, S. (Food and Agriculture Organization of the United Nations, 2001)
Broadening of basic germplasm pools can only achieve its goal of promoting agricultural stability if the products are actually sown by farmers on a significant scale.